Analysis of The Compensation System in Efforts to Increase Work Motivation at CV Wewe Travel, Malang City - Maria Sariyanti Hale; Yuni Setyawati; Imam Hidayat; Nur Ida Iriani (International Journal of Management and Business, 2026)
Effective human resource management through recruitment, training, develop-ment, and performance evaluation, has been shown to significantly enhance organization-al outcomes. This study aims to analyze the compensation system implemented at CV Wewe Travel in Malang City and to examine its impact on employee work motivation. The research was conducted at CV Wewe Travel, Malang, Indonesia. It conducted from January 22 to February 22, 2026. This study employed a qualitative research approach. The research at CV Wewe Travel, Malang City, demonstrates that the company’s com-pensation system comprising basic salary, incentives, bonuses, routine wage payments, and work facilities—functions flexibly to accommodate the operational characteristics of the transportation service business. While certain divisions, such as Customer Service, do not fully meet Regional Minimum Wage standards, timely wage payments and perfor-mance-based incentives reflect the company’s commitment to employee rights and productivity. The integration of financial and non-financial rewards, including recognition and provision of work facilities, has a significant positive impact on employee motivation. By fostering both extrinsic and intrinsic drivers of performance, the compensation system effectively supports responsibility, achievement, and overall organizational sustainability.